Quantifying the carbon footprint reduction potential of lifestyle choices in Japan - Yosuke Shigetomi; Keiichiro Kanemoto; Yuki Yamamoto; Yasushi Kondo (Environmental Research Letters, 2021)
Numerous studies have investigated the hotspots for reducing carbon emissions associated with household consumption, including reducing household carbon footprints (CFs) and greener lifestyle choices, such as living car-free, eating less meat, and having one less child. However, estimating the effect of each of these actions requires the simultaneous consideration of lifestyle choices and household characteristics that could also affect the household CF. Here, we quantify the reduction in household CFs for 25 factors associated with individual lifestyle choices or socioeconomic characteristics. This study linked approximately 42 000 microdata on consumption expenditure with the Japanese subnational 47 prefecture-level multi-regional input–output table, which are both the finest-scale data currently available. We improved the accuracy of household CF calculations by considering regional heterogeneity, and successfully estimated the magnitude of household CF reduction associated with individual lifestyle choices and socioeconomics. For example, it was found that moving from a cold region to a region with mild climate would have considerable potential for reducing the CO _2 emissions of a household, all other factors being equal. In addition, a household residing in a house that meets the most recent energy standards emits 1150 kg less CO _2 per year than if they reside in a house that meets previous energy standards. Ownership and use of durable goods also had the potential for reducing the CO _2 emissions of a household; a normal-sized car, a personal computer, a compact car, and a bidet were associated with CO _2 emissions of 922, 712, 421, and 345 kg per year, respectively. The findings therefore have important implications for climate change mitigation and policy measures associated with lifestyle.